Examination of the causal role of immune cells in non-alcoholic fatty liver disease by a bidirectional Mendelian randomization study - Li Yu; Lv Xiaodan; Lin Jianing; Li Shiquan; Lin Guangfu; Huang Zhixi; Chen Deyi; Han Lichun; Zhan Lingling; Lv Xiaoping (Open Medicine)
Non-alcoholic fatty liver disease (NAFLD) is a globally widespread disease. Recent investigations have highlighted a close association between immunity and NAFLD, but the causality between them has not been thoroughly examined.